FERROPTOSIS AND ITS POTENTIAL ROLE IN CARDIOVASCULAR DISEASES - Yavor Kashlov; Maria Dimova (Peytchinski Publishing, 2019)
Iron (Fe) is the fourth most common element in the earth's crust, and plays a significant role in the human body.It is important for cell survival due toits involvement in the transport of oxygen, in DNA biosynthesis, adenosine triphosphate (ATP) synthesis, as well as an auxiliary factor of various proteins in the tricarboxylic acid cycle (TCA). It has also been found that iron is closely related to the onset and progression of various cancers and disturbances in its metabolism can stimulate the growth of tumor cells. In addition, divalent iron significantly accelerates the lipid peroxidation of saturated fatty acids.